2010
DOI: 10.1111/j.1399-5448.2010.00655.x
|View full text |Cite
|
Sign up to set email alerts
|

Variables associated with severe hypoglycemia in children and adolescents with type 1 diabetes: a population-based study

Abstract: In these patients, a relatively low incidence of SH was recorded, without pronounced association with lower HbA1c or multiple daily injection insulin therapy. SH seems to be mainly related to management of diabetes. We believe that the main path to SH prevention is through patient and family education in the management of T1DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 53 publications
1
16
0
2
Order By: Relevance
“…Such advances could include the introduction, and increased use, of insulin analogues, CSII therapy, increased frequency of SMBG, continuous glucose monitoring (CGM), use of carbohydrate counting and calculators for insulin dose adjustments and improvements in patient education and management of hypoglycemia . Irrespective of such advances in modern diabetes therapies and technologies, the application of clinical recommendations and patient education remain critical in minimizing the risk of hypoglycemia in patients with type 1 diabetes . This includes effective patient/caregiver education regarding hypoglycemia awareness and management, strategies for appropriate dietary intake and exercise‐related insulin adjustments and the importance of self‐blood glucose monitoring .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such advances could include the introduction, and increased use, of insulin analogues, CSII therapy, increased frequency of SMBG, continuous glucose monitoring (CGM), use of carbohydrate counting and calculators for insulin dose adjustments and improvements in patient education and management of hypoglycemia . Irrespective of such advances in modern diabetes therapies and technologies, the application of clinical recommendations and patient education remain critical in minimizing the risk of hypoglycemia in patients with type 1 diabetes . This includes effective patient/caregiver education regarding hypoglycemia awareness and management, strategies for appropriate dietary intake and exercise‐related insulin adjustments and the importance of self‐blood glucose monitoring .…”
Section: Discussionmentioning
confidence: 99%
“…8,25,26 Irrespective of such advances in modern diabetes therapies and technologies, the application of clinical recommendations and patient education remain critical in minimizing the risk of hypoglycemia in patients with type 1 diabetes. 20,27 This includes effective patient/caregiver education regarding hypoglycemia awareness and management, strategies for appropriate dietary intake and exercise-related insulin adjustments and the importance of self-blood glucose monitoring. 20 Given the real risks associated with severe hypoglycemia, glycemic targets need to be individualized, taking into account the patient's age, comorbidities, lifestyle, personal/caregiver preferences, and the potential impact of hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive impairment associated with hypoglycemia may prevent a child from seeking help, so delaying treatment. Severe hypoglycemia is inversely associated with age and glycemic control , but is not strongly associated with duration of diabetes . Continuous glucose monitoring (CGM) has suggested that nocturnal hypoglycemia occurs approximately every third night and is associated with strict glycemic control and younger age .…”
mentioning
confidence: 99%
“…However, the frequency of hypoglycemia reported in this study might not reflect the real value, since it was calculated based on the data recorded by the patients or their relatives. Blasetti et al (23) performed a longitudinal study on 195 children with T1DM and followed them for 7.5 years. They reported that the rate of severe hypoglycemic attacks was 9.4% in one year and that hypoglycemic attacks were not associated with HbA1c levels, with daily insulin requirements, or with insulin regimens used.…”
Section: Discussionmentioning
confidence: 99%